Factors related to the occurrence of acute renal insufficiency in the intensive care unit: an integrative review (Research, Society and Development, 2020)
This study aimed to describe the clinical conditions, diagnostic and therapeutic interventions related to the occurrence of acute renal insufficiency in the intensive care unit. This is an integrative literature review study on articles published in the PubMed and LILACS databases. As for the results, 22 articles were selected and from them the ARI in the ICU was related to: sepsis, electrolyte disturbances, prematurity, obstetric complications and ARDS (clinical conditions); use of contrast to perform exams (diagnostic intervention) and nephrotoxic drugs, invasive mechanical ventilation, fluid overload (after surgery with the use of cardiopulmonary bypass (CPB) and surgical patient after pediatric surgery for myocardial revascularization and use of CPB (therapeutic interventions). Acute renal insufficiency in the ICU is related to the patient's profile and the interventions inherent to this sector. The physiological mechanisms involved in this complication can be triggered by the interventions that are necessary with the critical patient. This requires the adoption of protective conduct for renal function and the adoption of parameters for its monitoring.